PANDANGAN FILSAFAT TERHADAP IPTEK DALAM PENDIDIKAN SEKOLAH DASAR - Lina Marcelina; Desyandri; Yeni Erita (STKIP Subang, 2022)
This research is motivated by the basic concept that humans are never satisfied in anything, because humans as creatures of homo sapiens, animal educandum, ens metaphysicum, and homo religious always experience a process. As thinking beings (homo sapiens) humans always think, as students (animal educandum) humans always learn everything, as philosophical beings (ens metaphysics) humans do not accept raw knowledge received, as religious beings (homo religious) humans have confidence. Currently, humans face new challenges, namely dealing with the accelerated development of Science and Technology. The purpose of this research includes a description of science and technology (IPTEK) and describes the role of humans in the development of science and technology (IPTEK). The method used is descriptive analysis.